The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1111/j.1742-7843.2007.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Deramciclane, Ritanserin and Buspirone on Extracellular Dopamine and Its Metabolites in Striatum and Nucleus Accumbens of Freely Moving Rats

Abstract: Abstract:In the present study, we assessed the effect of single graded doses of a putative anxiolytic compound, the 5-HT 2A/C antagonist, deramciclane fumarate (EGIS-3886), on the dopamine efflux and metabolism in nucleus accumbens and striatum and thus evaluated the dose window for deramciclane to cause adverse effects related to the brain dopaminergic system. Dual probe in vivo microdialysis in freely moving rats was used to compare the effects of graded doses of deramciclane fumarate (3, 10 and 30 mg/kg), 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The tissue samples were frozen and stored at −70° C until being analyzed. DA levels in both striata were analyzed by a high performance liquid chromatography (HPLC) method with electrochemical detection (ECD) as previously described (Kääriäinen et al, ). The following modifications were made to adapt the method for tissue homogenate matrix.…”
Section: Methodsmentioning
confidence: 99%
“…The tissue samples were frozen and stored at −70° C until being analyzed. DA levels in both striata were analyzed by a high performance liquid chromatography (HPLC) method with electrochemical detection (ECD) as previously described (Kääriäinen et al, ). The following modifications were made to adapt the method for tissue homogenate matrix.…”
Section: Methodsmentioning
confidence: 99%
“…It could also be speculated that because of the higher affinity of endogenous DA for the DRD 3 (vs DRD 2 ), increases in DA would have interfered with buspirone in ƒD 3 more so than in ƒD 2 . However, several studies reported no significant effects of buspirone on DA release using microdialysis in striatal areas in rats (Kaariainen et al, 2008;Liu et al, 2004). In addition, the elevation of DA induced by acute antipsychotics is in the range of 100% (Ichikawa and Meltzer, 1991), and therefore it is unlikely that potential elevation of DA induced by buspirone would lead to significant occupancy of receptors as assessed by PET (Martinez and Narendran, 2010).…”
Section: Figurementioning
confidence: 97%
“…The attribution of buspirone-induced changes in (Rabiner et al, 2009), and (2) buspirone increases extracellular dopamine, which may differentially affect the binding of the two radiotracers (Gobert et al, 1999;Kaariainen et al, 2008 (Rabiner et al, 2009), which we attribute to both a small degree of D 2 R binding but also competition from endogenous dopamine released by buspirone (Gobert et al, 1999;Kaariainen et al, 2008). We also cannot exclude underestimation of D 3 R occupancy due to the presence of D 3 R in CB (Ginovart et al, 2007;Rabiner et al, 2009), which could affect occupancy measures when using [ 11 C]PHNO (Searle et al, 2013).…”
Section: Study Limitations and Other Considerationsmentioning
confidence: 99%